2020
DOI: 10.1111/cobi.13483
|View full text |Cite
|
Sign up to set email alerts
|

Positioning human heritage at the center of conservation practice

Abstract: Conservation projects subscribing to a community-based paradigm have predominated in the 21st century. We examined the context in which the phrase was coined and traced its growth over time. Communitybased conservation first appeared in the literature in the early 1990s; but grew little until after the 5th World Parks Congress in 2003. Thereafter, publications describing community-based conservation approaches increased exponentially. The conference theme was Benefits Beyond Boundaries, and its goal was to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 59 publications
(115 reference statements)
0
30
0
Order By: Relevance
“…Discrepancy in how much research has been conducted between the Global North and Global South regions raises concerns about the applicability of current scientific knowledge and implementation of conservation projects in low-income countries (Montgomery et al 2020). The Global South faces unique socio-political issues that can make research and implementation of conservation projects challenging (Montgomery et al 2020, Moussy et al 2021.…”
Section: List Of Figuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Discrepancy in how much research has been conducted between the Global North and Global South regions raises concerns about the applicability of current scientific knowledge and implementation of conservation projects in low-income countries (Montgomery et al 2020). The Global South faces unique socio-political issues that can make research and implementation of conservation projects challenging (Montgomery et al 2020, Moussy et al 2021.…”
Section: List Of Figuresmentioning
confidence: 99%
“…Discrepancy in how much research has been conducted between the Global North and Global South regions raises concerns about the applicability of current scientific knowledge and implementation of conservation projects in low-income countries (Montgomery et al 2020). The Global South faces unique socio-political issues that can make research and implementation of conservation projects challenging (Montgomery et al 2020, Moussy et al 2021. For instance, armed conflicts (Gaynor et al 2016), ineffective governance (Baynham-Herd et al 2018), and human-wildlife conflicts (Michalski et al 2020) in the Global South have been shown to negatively affect wildlife.…”
Section: List Of Figuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Such efforts have involved assessments of human perceptions, attitudes, and normative behaviors in relation to wildlife, compensation schemes for property loss caused by wildlife, fortification of enclosures promoting food security, and various measures designed to alter animal movement and behavior in relation to human-dominated landscapes (Madden 2004 ; Hoffmann et al 2017 ; Kissui et al 2019 ; Meena 2020 ). However, the efficacy of these interventions are seldom assessed, contributing to evident divides among the research and policy spheres (Kapos et al 2009 ; Artelle et al 2018 ; Montgomery et al 2020b ). Such ‘knowing-doing’ or ‘research-implementation’ gaps hamper efforts to protect human interests and can simultaneously stymie conservation practice (Knight et al 2008 ; Montgomery et al Montgomery et al 2018b ; Gray et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Madden and McQuinn (2014) argue that "conservation efforts would benefit from improved capacity and resources for understanding and transforming the complex drivers of deep-rooted social conflicts impacting wildlife conservation and management actions" (p. 104). Numerous scholars have made a strong case that biodiversity conservation is ultimately a social and political process (Brechin et al, 2002;Lele et al, 2010;Montgomery et al, 2020). Yet, despite a growing body of research focused on the social component of social-ecological systems (Ban et al, 2013), including systems with carnivore species such as tigers (Torri, 2011;Struebig et al, 2018), efforts to apply this research by re-conceptualizing and adapting conventional conservation approaches have been slow (Bennett et al, 2017).…”
Section: Introductionmentioning
confidence: 99%